Green Marketing Communication as a Strategy for Sustainable Brand Image Formation at Maida Coffee - Viktorianus Mahendra Da Lopez; Yonas Ferdinand Riwu; Achwan Noorlistyo Adi (Dinasti International Journal of Education Management and Social Science, 2025)
This study examines the implementation of green marketing at Maida Coffee Shop, a local micro-business in Kupang, Indonesia, that has built a reputation for environmental concern despite its operational scale. The research addresses how the coffee shop integrates sustainability principles into its marketing and operational practices. Using a descriptive qualitative method, data were collected through in depth interviews with the owner and direct observation. The findings reveal that Maida Coffee actively constructs a green brand identity through strategic environmental communication, notably its "Saving Forests Through Coffee" (“Menjaga Hutan Lewat Kopi”) campaign, and robust collaborations with environmental communities. These efforts are central to its brand narrative. However, a gap exists between this communicated environmental awareness and its operational practices. Limitations in waste management, energy efficiency, and the adoption of biodegradable packaging were identified, primarily constrained by cost, technology, and local consumer purchasing power. The study concludes that while Maida Coffee effectively uses narrative and communication to build a sustainable brand image, it is in a transitional phase toward more comprehensive green business practices. Recommendations focus on strengthening operational consistency, inclusive pricing strategies, and enhanced consumer education to align its green identity with tangible actions